Social vulnerability and mediation of information in the prison context: interrelationships and perceptions - Sousa, Francisca Liliana Martins de (2020)
It presents a literature review based on the social and interdisciplinary assumption of Information Science (IC), which aims to discuss social vulnerability in the context of deprived freedom subjects, connecting information mediation and the librarian as assets to reduce this fragility. From a bibliographic survey that guided the accomplishment of this study, we present concepts and characteristics of vulnerability relating situations experienced in the prison environment and ratifying the inclusion of this group as socially vulnerable. It deals with the insertion of the librarian in penal establishments, based on the legal determination of the existence of prison libraries in these spaces. The research results indicate that this professional would act as a mediating agent, planning and building for and with the incarcerated subject actions that favor social reintegration. However, it must be understood that due to the characteristics of the information environment portrayed, specific skills are required for the librarian to effectively perform his or her role in the prison environment. It is concluded that the paradigm shift in the function of prisons still cannot be applied in practice. IC as a social and interdisciplinary science can contribute to actions and discussions about the phenomenon of information in this environment, favoring the social reintegration of graduates.